The Effect of Environmental Contexts on Motor Proficiency and Social Maturity of Children: An Ecological Perspective - Zahra Fathirezaie; Kosar Abbaspour; Georgian Badicu; Seyed Hojjat Zamani Sani; Hadi Nobari (Children, 2021)
Physical environmental factors affect the developmental process of children. Thus, the main purpose of the present study was to investigate the two intervention models of affordances on the motor proficiency and social maturity of children. A semi-experimental research design with a pretest–posttest design and two groups were used, adopting the convenience method. Two groups of 15 children (aged 5.5–6.5 years) engaged in 12 weeks of nature school or kindergarten. The Bruininks–Oseretsky test of motor proficiency and the Vineland social maturity scale were used. The results of a mixed ANOVA showed that natural outdoor activity has a greater positive effect on motor proficiency and social maturity than kindergarten activities. Intra-group analysis also showed that both groups had progressed, but the nature school group made more progress. These results were discussed and interpreted based on the types of environmental affordances, Gibson’s theory, Bronfenbrenner theory, and child-friendly environment. It was suggested that natural environmental stimulations play a critical role in optimal child motor and social development during the early stages of life.